Politik Uang pada Pemilihan Bupati dan Wakil Tahun 2020 di Kabupaten Mandailing Natal - Linda Mora; Tengku Rika Valentina; Zainal Arifin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to describe the process of vote buying and selling at 2 TPS in Kampung Baru Village and analyze the political relations of incumbent candidates in Kampung Baru Village. This research uses a qualitative descriptive approach with a case study method. The theories used are vote buying, patronage, and clientelism. The research results show that vote buying at 2 TPS in Kampung Baru Village stems from low voter participation. There were 216 voters who came to exercise their voting rights out of 872 voters. Seeing the low voter participation, the Head of Kampung Baru Village as the incumbent's success team asked the KPPS to vote on the remaining ballot papers. KPPS officers agreed and asked the incumbent's success team to discuss it with the PPS chairman of Kampung Baru Village. The results of the negotiations between the PPS chairman and the Village Head resulted in an agreement to buy and sell 400 votes in exchange for Rp. 30,000/ballot paper. The patronage relationship between incumbent candidates and KPPS and PPS officers in Kampung Baru Village occurs through the clientelism network of the Village Head as a liaison mediator who reconciles the political interests of the incumbent with the needs of the organizers. The implications of money politics on the integrity of the regional election organizers and results damage the image and good name of the institution, reduce public confidence in the election organizers and results, damage the quality of the democratic election process and results, disrupt the election implementation scheme and weaken the political legitimacy of the people.